Congenital pulmonary varix: Two case reports. Issue 51 (23rd December 2021) - Maruyama, Takuji; Kariya, Shuji; Nakatani, Miyuki; Ono, Yasuyuki; Ueno, Yutaka; Komemushi, Atsushi; Tanigawa, Noboru
Abstract: Rationale: Patients with congenital pulmonary varix are asymptomatic and require no treatment, but the radiological characteristics of a pulmonary varix are similar to those of a pulmonary arteriovenous malformation, which requires treatment. Pulmonary angiography is useful for obtaining information about the dynamics of pulmonary blood flow to differentiate a pulmonary varix from a pulmonary arteriovenous malformation for the purpose of treatment planning. Two cases of congenital pulmonary varices that were differentiated from pulmonary arteriovenous malformations based on pulmonary angiography findings are presented. Patient concerns and diagnosis: The first patient was an asymptomatic 39-year-old man. Non-contrast-enhanced computed tomography performed as part of the treatment course for pneumonia showed pulmonary arteriovenous malformation in the right lung. Pulmonary angiography was performed and showed that it was a pulmonary varix. The second patient was an asymptomatic 23-year-old woman. As part of her regular health check-up, she underwent plain chest X-ray examination, which showed an abnormal shadow. Non-contrast-enhanced computed tomography was performed, and pulmonary arteriovenous malformation was suspected. However, contrast-enhanced computed tomography findings suggested that the patient had a congenital pulmonary varix rather than a pulmonary arteriovenous malformation. Pulmonary angiography was subsequently performed for diagnosis, and a pulmonary varix was confirmed. Interventions and outcomes: No treatment was administered to either patient. The first patient was followed up for four years, and the second patient for two years. Both patients had no symptoms or complications during the follow-up period. Lessons: Two cases of congenital pulmonary varices were reported. Information about the dynamics of pulmonary blood flow obtained by performing pulmonary angiography was effective in distinguishing between pulmonary arteriovenous malformation and congenital pulmonary varix.